Control of Mesoscale Morphology and Photovoltaic Performance in Diketopyrrolopyrrole‐Based Small Band Gap Terpolymers. Issue 3 (26th October 2016) - Ye, Long; Jiao, Xuechen; Zhang, Shaoqing; Yao, Huifeng; Qin, Yunpeng; Ade, Harald; Hou, Jianhui
Abstract : Morphology control is one of the key strategies in optimizing the performance of organic photovoltaic materials, particularly for diketopyrrolopyrrole (DPP)‐based donor polymers. The design of DPP‐based polymers that provide high power conversion efficiency (PCE) presents a significant challenge that requires optimization of both energetics and morphology. Herein, a series of high performance, small band gap DPP‐based terpolymers are designed via two‐step side chain engineering, namely introducing alternating short and long alkyls for reducing the domain spacing and inserting alkylthio for modulating the energy levels. The new DPP‐based terpolymers are compared to delineate how the side chain impacts the mesoscale morphology. By employing the alkylthio‐substituted terpolymer PBDPP‐TS, the new polymer solar cell (PSC) device realizes a good balance of a high V oc of 0.77 V and a high J sc over 15 mA cm −2, and thus realizes desirable PCE in excess of 8% and 9.5% in single junction and tandem PSC devices, respectively. The study indicates better control of domain purity will greatly improve performance of single junction DPP‐based PSCs toward 10% efficiency. More significantly, the utility of this stepwise side chain engineering can be readily expanded to other classes of well‐defined copolymers and triggers efficiency breakthroughs in novel terpolymers for photovoltaic and related electronic applications. Abstract : A new class of small band gap terpolymers featuring diketopyrrolopyrrole unit are designed and their mesoscale morphology are well‐correlated with device characteristics. The alkylthio‐substituted terpolymer PBDPP‐TS exhibits deep highest occupied molecular orbital energy level and optimal domain characteristic length/domain purity, resulting in over 8% and 9.5% efficiency for single junction and tandem polymer solar cells, respectively.